Simultaneous consideration of the balancing market and day-ahead market in Stackelberg game for flexiramp procurement problem in the presence of the wind farms and a DR aggregator - Kaheh, Zohreh; Kazemzadeh, Reza Baradaran; Sheikh-El-Eslami, Mohammad Kazem (IET generation, transmission & distribution, 2019)
This study presents a cooperative bidding model for energy, reserve, and flexiramp providing by a group of suppliers. Procurement problems in electricity markets have been analysed through the Stackelberg concept and modelled via bi-level programming. However, previous bi-level models have captured the game only in the context of the day-ahead or real-time market. In this study, a stochastic two-stage multi-objective bi-level model for procurement problem in the day-ahead and balancing markets is proposed; in which the Stackelberg game is simultaneously considered in these markets. In each stage of the proposed model, multiple decision-makers including conventional and wind generating units as well as a demand response (DR) aggregator act as leaders, and independent system operator (ISO) acts as a follower. The presented model for DR aggregator determines some important parameters dynamically considering the hourly locational marginal prices and the behaviour of the small-size consumers. To solve the model, two reformulation schemes are presented: (i) a Karush Kuhn Tucker (KKT) method with some linearisation approaches and (ii) a fuzzy max–min technique. The proposed model is applied to the 24-bus IEEE test system to demonstrate the effects of the Stackelberg game in balancing market on the day-ahead market's equilibriums and benefits of implementing the proposed model in electricity markets.